Small calcified lesions suggestive of neurocysticercosis are associated with mesial temporal sclerosis - Oliveira, Marcos Castello Barbosa de; Martin, Maria da Graça Morais; Tsunemi, Miriam Harumi [UNESP]; Vieira, Gilson; Castro, Luiz Henrique Martins (Assoc Arquivos Neuro- Psiquiatria, 2014)
Recent studies have suggested a possible relationship between temporal lobe epilepsy with mesial temporal sclerosis (MTS) and neurocysticercosis (NC). We performed a case-control study to evaluate the association of NC and MTS. Method: : We randomly selected patients with different epilepsy types, including: MTS, primary generalized epilepsy (PGE) and focal symptomatic epilepsy (FSE). Patients underwent a structured interview, followed by head computed tomography (CT). A neuroradiologist evaluated the scan for presence of calcified lesions suggestive of NC. CT results were matched with patients'data. Results: : More patients in the MTS group displayed calcified lesions suggestive of NC than patients in the other groups (p=0.002). On multivariate analysis, MTS was found to be an independent predictor of one or more calcified NC lesions (p=0.033). Conclusion: : After controlling for confounding factors, we found an independent association between NC calcified lesions and MTS.

Estudos recentes têm sugerido possível relação entre epilepsia do lobo temporal com esclerose mesial temporal (MTS) e neurocisticercose (NC). Conduzimos um estudo caso-controle para avaliar a associação de NC e MTS. Método: Selecionamos randomicamente pacientes com diferentes tipos de epilepsia, incluindo: MTS, epilepsia primariamente generalizada (PGE) e epilepsia focal sintomática (FSE). Pacientes foram submetidos a uma entrevista estruturada, seguida por uma tomografia computadorizada de crânio (CT). Um neuroradiologista avaliou as imagens quanto à presença de lesões calcificadas sugestivas de NC. Resultados das CT foram comparados com os dados dos pacientes. Resultados: Mais pacientes do grupo MTS apresentaram lesões calcificadas sugestivas de NC que de outros grupos (p=0,002). Na análise multivariável, MTS foi um preditor independente de uma ou mais calcificações sugestivas de NC (p=0,033). Conclusão: Após controlar para fatores confusionais, encontramos uma associação independente entre lesões calcificadas de NC e MTS.
Pequenas lesões calcificadas sugestivas de neurocisticercose e estão associadas com esclerose mesial temporal
Keywords: Hippocampal sclerosis; Cysticercosis; Temporal lobe epilepsy; Mesial temporal sclerosis; Neurocysticercosis; Calcifications; Esclerose de hipocampo; Cisticercose; Epilepsia do lobo temporal; Esclerose mesial temporal; Neurocisticercose; Calcificações